ANALISIS KELAS KESESUAIAN LAHAN UNTUK PENGEMBANGAN TANAMAN BAWANG MERAH (Allium ascalonicum L) - Yovita Yasintha Bolly; M.A. Yohanita Nirmalasari (AGRICA, 2020)
Shallot (Allium ascalonicum L) is one type of horticultural crop which is considered good for farmers to cultivate. This commodity to be able to grow and produce optimally requires land quality and certain characteristics and management. It is necessary to evaluate the suitability of the land to predict land use in accordance with the requirements of a plant, so that it is expected to be able to increase the productivity of onion plants. The practice garden of the Faculty of Agriculture, University of Nusa Nipa (UNIPA) Maumere is a practice location for Faculty of Agriculture students. The land is intended for cultivation of food crops and horticulture. The purpose of this study was to determine the suitability of land onion plant development. This research has been carried out in the Faculty of Agriculture UNIPA practice garden. The method used is the arithmetic matching method by matching the observations in the laboratory and field with the requirements for growing shallots. The results of this study indicate that the overall practice of the Faculty of Agriculture at the University of Nusa Nipa Maumere has similarity in land suitability classes, namely very suitable class (S1) with limiting factors such as temperature (tc), rainfall (wa), texture (t), drainage (d), soil depth (k), C-Organic, total N, P2O5, K2O, surface slope (l), erosion hazard, and rock conditions (b). This shows that the practice garden of the Faculty of Agriculture, University of Nusa Nipa Maumere is very suitable for agricultural cultivation activities for shallots.